Preoperative Predictors of Weight Loss After Sleeve Gastrectomy - Mohammed, Ali H.; Al-Ali, Mohammed H.; Al-Saffar, Samir I. (Scientific Journal of Medical Research, 2021)
Background: There are many preoperative factors like (age, BMI, gender, eating habit, marital status) that may affect weight loss after bariatric surgery and the prediction of these factors is important to improve weight loss and satisfy patient expectation. Objective: Assessment of obese patients who underwent sleeve gastrectomy with regards to the factors that may affects weight loss, so surgeons and patients can predict the outcome. Patients and Methods: Sixty one patients underwent laparoscopic sleeve gastrectomy in Aljamhory teaching hospital and AlZahrawi private hospital in Mosul; their data collected of initial weight, age, gender, marital state, co morbidity and diet habit. Results: The mean weight loss was 19, 35, 42.9 kg during 3 ,6,12th months interval which is equal to 34 ,60 and 75 percent EBW loss and the final percent of EBW loss ranges between 13.4-117.9 ,and mean percent of EBW loss was found to be 29, 39.5, 83 percent in males and 31, 52, 69.7 percent in females at 3rd, 6th, 12th months intervals, respectively. Conclusion: Initial weight, BMI and male gender can be regarded as a preoperative predictor factors for significant weight loss after sleeve gastrectomy, while marital state, diet habit, age and co morbidity cannot.